Using version control to document genuine effort in written assignments: a protocol with examples for universities - Orbán, Levente L. (Frontiers in Education, 2023)
This conceptual report describes a novel assessment technique to evaluate written assignments in universities, such as literature reviews, essays or research proposals, over the course of the academic semester in multiple milestones. The method can be adapted to undergraduate and graduate courses in disciplines with a writing requirement. Key features of this method include encouraging student self-regulation and spacing of learning, rapid scoring using quantitative elements, improving the authenticity and transparency of the written work, and guiding students towards better writing and thinking skills. The method involves the implementation of a system called version control, which is a class of software to track and manage changes to textual data, often used by programmers to track code. This report describes a use case in two psychology courses describing the logistics and marking dynamics surrounding the assessment. This protocol has been seeded on a public repository on GitHub where educators can contribute and develop the technique further.